Fangtastic! - Mercer, Sienna (New York : HarperTrophy, 2007)
Eighth-grade twins Olivia and Ivy and their friends try to prevent a nosy television reporter, Serena Star, from uncovering the secret community of vampires in Franklin Grove.
Ages 8-12.
760
Accelerated Reader AR
Keywords: Vampires -- Juvenile fiction; Sisters -- Juvenile fiction; Twins -- Juvenile fiction; Reporters and reporting -- Juvenile fiction; Tabloid newspapers -- Juvenile fiction; Schools -- Juvenile fiction